Youth as Environmental Custodians: A Potential Tragedy or A Sustainable Business and Livelihood Model? - Stein T. Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2016)
Youth unemployment and migration is a growing challenge that needs more political attention in many countries in the world, particularly countries with rapid population growth and economic transformation. Proactively mobilizing the youth as a resource in the creation of sustainable livelihoods can potentially be a win-win-win solution that Ethiopia is currently attempting with its new youth employment strategy and high ambitions to transform the country's economy into a Green Economy. If it succeeds, it can set an example for other countries in the world to follow. This paper gives and overview of the youth program and the basic ideas and challenges.
Keywords: J08; J21; M13; Q15; Q23; 330; Youth; youth migration; unemployment; area exclosures; common property resource management; environmental custodians; collective action; business model